2004
DOI: 10.1080/0964056042000274434
|View full text |Cite
|
Sign up to set email alerts
|

The firm, environmental management and environmental measures: Lessons from a survey of European manufacturing firms

Abstract: This paper reports on the results of a survey of environmental management and technical measures amongst almost 2000 European firms. Logit analysis is undertaken to determine the effects of firm characteristics, commercial conditions, perceived environmental impacts, expected benefits and stakeholder pressures on the probability of having an environmental management system in place. Subsequently, determinants of the likelihood of undertaking environmental actions in five environmental areas are estimated. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…There has been ongoing debate as to whether it is worthwhile to be "green", or environmentally proactive, with mixed findings reported in relation to the association between EMSs and environmental performance (Iraldo et al, 2009;Hertin et al, 2008;Johnstone et al, 2004;Melnyk et al, 2003). Such mixed findings can be attributed to the way in which EMSs and environmental performance have been operationalised in prior studies.…”
Section: Introductionmentioning
confidence: 77%
“…There has been ongoing debate as to whether it is worthwhile to be "green", or environmentally proactive, with mixed findings reported in relation to the association between EMSs and environmental performance (Iraldo et al, 2009;Hertin et al, 2008;Johnstone et al, 2004;Melnyk et al, 2003). Such mixed findings can be attributed to the way in which EMSs and environmental performance have been operationalised in prior studies.…”
Section: Introductionmentioning
confidence: 77%
“…He found, however, little evidence that EMS is a strong autonomous driver for performance improvement. In their econometric analysis of the data obtained through a survey of 2000 European companies, Johnstone et al (2004) found that EMSs (including both ISO 14001 and EMAS) played ''a distinct role in encouraging firms to undertake measures to improve their environmental performance in a number of areas.'' The impact of EMS was particularly important in the generation of waste water and air emissions and in the reduction of environmental impacts from accidents.…”
Section: Ems and Environmental Performancementioning
confidence: 99%
“…Moreover, they were asked to identify possible incentives for implementing ISO 14001. The questionnaire was distributed to selected enterprises via mail, e-mail, fax, and mostly face-to-face to respondents who would be more knowledgeable to answer the survey questions, alike previous survey-based studies on environmental management [25,27]. The response rate of comparable studies addressing already certified firms ranged between 17 and 81% [11,30,32,44].…”
Section: Instrumentsmentioning
confidence: 99%
“…It requires that adopting organizations create an environmental policy, set objectives and targets, implement a program to achieve those objectives, monitor and measure the program's effectiveness, correct problems, and conduct reviews aimed at improving the EMS. As such, the EMS is a tool that allows the continual improvement of the environmental behavior and performance [11,16,25,29].…”
Section: Introductionmentioning
confidence: 99%